2021
DOI: 10.1021/acsami.1c12423
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Electron Affinity and Interfacial Charge Transfer of Graphene for Self-Powered Nonenzymatic Biosensor Applications

Abstract: Facile electron transport and intimate electronic contact at the catalyst–electrode interface are critical for the ideal performance of electrochemical devices such as glucose biofuel cells and biosensors. Here, through a comprehensive experimental–theoretical exploration, we demonstrate that engineering of interfacial properties, including interfacial electron dynamics, electron affinity, electrode–catalyst–adsorbate electrical synergy, and electrocatalytically active surface area, can lead to highly efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Sanad and coworkers deposited Sm 2 O 3 particles (see Figure 11a) on GA, and explored its electrocatalytic performance for glucose oxidation (Figure 11b) and ORR compared to an analogous Sm 2 O 3 /rGO sample. [16] Sm 2 O 3 /GA presented a good electrocatalytic behaviour developing a glucose oxidation current of 0.62 mA and an ORR activity with an onset potential of 0.8 V and a half-wave potential of 0.75 V vs RHE. From the comparison between Sm 2 O 3 /rGO and Sm 2 O 3 /GA the authors concluded that the faster electron transfer in the latter is attributable to the already mentioned higher electronic conductivity of GA.…”
Section: Nanoparticles and Single Metal Atoms Immobilization On Graph...mentioning
confidence: 99%
See 4 more Smart Citations
“…Sanad and coworkers deposited Sm 2 O 3 particles (see Figure 11a) on GA, and explored its electrocatalytic performance for glucose oxidation (Figure 11b) and ORR compared to an analogous Sm 2 O 3 /rGO sample. [16] Sm 2 O 3 /GA presented a good electrocatalytic behaviour developing a glucose oxidation current of 0.62 mA and an ORR activity with an onset potential of 0.8 V and a half-wave potential of 0.75 V vs RHE. From the comparison between Sm 2 O 3 /rGO and Sm 2 O 3 /GA the authors concluded that the faster electron transfer in the latter is attributable to the already mentioned higher electronic conductivity of GA.…”
Section: Nanoparticles and Single Metal Atoms Immobilization On Graph...mentioning
confidence: 99%
“…Very recently, Sanad and coworkers took advantage of the catalytic potential and good electron conduction of GA to develop an electrocatalyst able to carry out the non‐enzymatic glucose oxidation reaction and the oxygen reduction reaction (ORR), achieving improved performance compared to rGO [16] . These authors concluded that the increased number of COOH groups on GA compared to rGO resulted in a significantly higher ORR activity with an onset potential of 0.8 V, the highest reported for graphenic materials.…”
Section: The Uses Of Graphene Acidmentioning
confidence: 99%
See 3 more Smart Citations